Constitutive expression of cyclotide kalata B1 gene in transgenic rice conferring resistance to golden apple snail (Pomacea canaliculata) - Norsharina Md Saad; Chee, How Teo; Zuraida Ab Rahman; Zamri Zainal (Penerbit Universiti Kebangsaan Malaysia, 2023)
The golden apple snail, also known as Siput Gondang Emas in Malaysia, is a serious pest of paddy fields and native aquatic plants throughout Southeast Asia. Agrobacterium-mediated transformation was used to transform a synthetic Oak 1 gene encoding kalata B1 (kB1), which is toxic to golden apple snails, into Malaysian indica rice MR219. The synthetic Oak 1 gene was placed under the control of a strong constitutive Zea mays ubiquitin promoter. Twelve transgenic lines containing the Oak 1 gene were obtained from the regenerated calli selected on hygromycin. Oak 1 gene expression was determined using quantitative reverse transcriptase- PCR (RT-qPCR). The resistance of the transgenic line to snail infestation was evaluated by feeding experiments. One dimensional 1H nuclear magnetic resonance (NMR) spectroscopy revealed that the kB1 produced in transgenic rice is in the form of an acyclic peptide. Phenotypic analysis of the transgenic plants revealed that they have fewer leaves and grains than wild-type MR219. In a molluscicidal activity bioassay, feeding juvenile snails with different concentrations of leaf extracts resulted in molluscicidal activity against snails that was comparable to the synthetic molluscicide metaldehyde, thus farmers can overcome the golden apple snail infestation problem by using genetically modified rice containing the kB1-encoding gene. This technology also has the potential to reduce the toxic effects of chemically synthesized molluscicides on the environment and ecosystem.